Open innovation strategies in SMEs: development of a business model - Rahman, Md. Hakikur (2011)
Open innovation in entrepreneurships already ﬁnds its acceptance at all levels of the business industry for adding value to the business. The value could be in the form of economic gain or enhancement of knowledge leading to a sustained ﬁnancial base. Open innovation adopts various strategies to accom- plish the task for enhancing the value gain. Varying by size, nature, pattern, or characteristics of the ﬁrm various strategies are being adopted by enterprises. Though largely known to be familiar in corporate business houses, in recent years open innovation is also becoming increasingly familiar in small and medium enterprises (SMEs) and the trend is rapidly increasing. However despite the potency of open innovation strategies, most of the enterprises are yet to ﬁnd a sustained business model, especially for the SMEs working at the periphery of that value chain. This forms the basis of the current study. This chapter is trying to formulate a business model incorporating partnership approach from academia, research houses, intermediaries, and other stakeholders.